Molecular Correlates of Genes Exhibiting RNAi Phenotypes in Caenorhabditis elegans - Cutter, Asher D.; Payseur, Bret A.; Salcedo, Tovah; Estes, Anne M.; Good, Jeffrey M.; Wood, Elizabeth; Hartl, Thomas; Maughan, Heather; Strempel, Jannine; Wang, Baomin; Bryan, Anthony C.; Dellos, Melissa (Genome Research, 2003)
Understanding genome-wide links between genotype and phenotype has generally been difficult due to both the complexity of phenotypes, and until recently, inaccessibility to large numbers of genes that might underlie a trait. To address this issue, we establish the association between particular RNAi phenotypes in Caenorhabditis elegans and sequence characteristics of the corresponding proteins and DNA. We find that genes showing RNAi phenotypes are long and highly expressed with little noncoding DNA and high rates of synonymous site substitution (KS). In addition, genes conferring RNAi phenotypes have significantly lower rates of nonsynonymous site substitution (KA). Collectively, these sequence features explain nearly 20% of the difference between the sets of loci that display or lack a RNAi-mediated effect, and reflect aspects both of the RNAi mechanism and the biological function of the genes. For example, the particularly low rate of evolution of genes in the sterility RNAi phenotype class suggests a role of C. elegans life history in shaping these patterns of sequence and expression characteristics on phenotypes. This approach also allows prediction of a set of heretofore-uncharacterized loci for which we expect future RNAi studies to reveal phenotypic effects (i.e., false negatives in present screens).